Ectopic Thoracic Kidney and End-Stage Renal Disease in a 38-Year-Old Nigerian - U. E. Ekrikpo; E. E. Effa; E. E. Akpan (Case Reports in Nephrology)
This patient is a 38-year-old housewife who presented with a one-month history of difficulty, in breathing, chest pain and bilateral leg swelling and had a blood pressure of 260/150 mmHg, features of malignant hypertension and hypertensive heart disease. Chest CT scan revealed a chest location of the left kidney. She also had elevated serum urea and creatinine and proteinuria (++). The right kidney was normally located with loss of corticomedullary differentiation. She is on maintenance haemodialysis and is being worked up for possible left nephrectomy.